Surface Lime Application in Long-Term No-Till Crop Production with Stratified Soil pH - F. D. Hansel; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2019)
Lime application is a key management strategy to control the acidifying effects promoted by long-term application of nitrogen (N) fertilizers and is also a source of calcium for the crops. Two field studies located in Mitchell County was carried out during 3 years (2016-2018), exploring the effect of lime application in wheat (first year), corn (second year), and soybean (third year) crops. After the first year, there was an increase in wheat yield of up to 8% with lime application. For corn (second year), liming showed a yield response of up to 10%. Soybean (third year) yield response to lime showed a 17% yield increase in one location, however, soybean yield response was inconsistent at the second location. The magnitude of response to lime application would be dependent on the initial soil pH and the sensitivity of the crop to low soil pH. Results from this study showed that lime applied to the surface (and not incorporated), can result in yield response. However, soil pH stratification after multiple years of no-till with surface N fertilizer application, showed low soil pH only near the surface, and the soil profile maintained optimum pH levels at these locations.
Keywords: soil pH; soil acidity; liming